Marine microbiology: ecology & applications - C. B. Munn (Boca Raton, Florida : CRC Press, 2020)
"The third edition of this bestselling text has been rigorously updated to reflect major new discoveries and concepts since 2011, especially progress due to extensive application of high-throughput sequencing, single cell genomics and analysis of large datasets. Significant advances in understanding the diversity and evolution of bacteria, archaea, fungi, protists, and viruses are discussed and their importance in marine processes is explored in detail. Now in full colour throughout, all chapters have been significantly expanded, with many new diagrams, illustrations and boxes to aid students' interest and understanding. Novel pedagogy is designed to encourage students to explore current high-profile research topics. Examples include the impacts of rising COb2 (Blevels on microbial community structure and ocean processes, interactions of microbes with plastic pollution, symbiotic interactions, and emerging diseases of marine life. This is the only textbook addressing such a broad range of topics in the specific area of marine microbiology, now a core topic within broader Marine Science degrees. A Companion Website provides additional online resources for instructors and students, including a summary of key concepts and terminology for each chapter, links to further resources, and flashcards to aid self-assessment."s
Keywords: Marine Biology